2018
DOI: 10.1038/s41467-018-03054-w
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: A PRDX1 mutant allele causes a MMACHC secondary epimutation in cblC patients

Abstract: The original version of this Article contained an error in the title, which was incorrectly given as "APRDX1 mutant allele causes a MMACHC secondary epimutation in cblC patients". This has now been corrected in both the PDF and HTML versions of the Article to read "A PRDX1 mutant allele causes a MMACHC secondary epimutation in cblC patients".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Interestingly, putative HCFC1 binding sites were also identified in the promoters of MTR and ABCD4 ; however, analysis of RNA and protein expression of these genes in fibroblasts showed no difference between HCFC1 patients and controls . In an alternative mechanism, loss of MMACHC expression has been described to be due to mutation of its neighbouring antisense oriented gene PRDX1 , which causes hypermethylation of the promoter and first exon of MMACHC and thereby causes MMACHC silencing . Thus far, no other regulatory mechanisms have been described for proteins proximal to MMACHC in the intracellular Cbl pathway (ie, LMBD1 and ABCD4) or in the mitochondrial pathway (ie, MMAA, MMAB, MMADHC, and MUT).…”
Section: Allosteric Genetic and Epigenetic Regulationmentioning
confidence: 99%
“…Interestingly, putative HCFC1 binding sites were also identified in the promoters of MTR and ABCD4 ; however, analysis of RNA and protein expression of these genes in fibroblasts showed no difference between HCFC1 patients and controls . In an alternative mechanism, loss of MMACHC expression has been described to be due to mutation of its neighbouring antisense oriented gene PRDX1 , which causes hypermethylation of the promoter and first exon of MMACHC and thereby causes MMACHC silencing . Thus far, no other regulatory mechanisms have been described for proteins proximal to MMACHC in the intracellular Cbl pathway (ie, LMBD1 and ABCD4) or in the mitochondrial pathway (ie, MMAA, MMAB, MMADHC, and MUT).…”
Section: Allosteric Genetic and Epigenetic Regulationmentioning
confidence: 99%
“…First, we asked whether some epivariations segregate within the population on specific haplotype backgrounds. 7,9 Using data from 933 individuals from the Women's Health Initiative in whom both methylation and single-nucleotide variation (SNV) data derived from bead arrays were available, we identified 97 epivariations that were present in at least two individuals, and performed association analysis of these with local SNVs. Overall, using a stringent statistical threshold (1% FDR), 68 of the 97 epivariations tested (70%) showed at least one significantly associated SNV (Figure 4, Table S10).…”
Section: Segregation Of Epivariations With Local Sequence Variantsmentioning
confidence: 99%
“…12 Primary epivariations are thought to be caused by stochastic errors in the establishment or maintenance of the epigenome, such as certain types of imprinting anomalies. 13 In contrast, secondary epivariations occur as a result of an underlying change in local DNA sequence and include mutations that disrupt regulatory elements 9,10,14 and expansions of CpG-rich tandem repeats. 15 Large hypermethylated expansions of CGG repeats have been identified at a number of folate-sensitive fragile sites in the human genome, 16 including several that are associated with neurodevelopmental anomalies, such as the CGG expansions that occur at FMR1 (MIM: 309550), AFF2 (MIM: 300806), DIP2B (MIM: 611379), and AFF3 (MIM: 601464).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxidases (PRDXs) are important antioxidant proteins that form a powerful defense system that maintains redox balance by converting hydrogen peroxide to water [ 60 ]. PRDX1 belongs to the PRDX family and is a 23-kDa stress-induced macrophage redox protein that has multiple functions, including managing hydrogen peroxide-mediated oxidative stress in vitro and in vivo, and is a potential target for breast cancer treatment [ 61 63 ]. Recently, it was shown that PRDX1 can reduce ROS and inhibit apoptosis induced by the MAPK signaling pathway [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%